Smart Education and e-Learning 2017 - Uskov, Vladimir L.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers the contributions presented at the 4th International KES Conference on Smart Education and Smart e-Learning (KES-SEEL-17), which took place in Vilamoura, Algarve, Portugal, June 21-23, 2017. Smart education and smart e-Learning are emerging and rapidly growing areas. They represent the innovative integration of smart systems, technologies and objects, smart environments, smart pedagogy, smart learning and academic analytics, various branches of computer science and computer engineering, and state-of-the-art smart educational software and/or hardware systems. It contains a total of 48 peer-reviewed book chapters that are grouped into several parts: Part 1 - Smart Pedagogy, Part 2 - Smart e-Learning, Part 3 - Systems and Technologies for Smart Education, Part 4 - Smart Teaching, and Part 5 - Smart Education: National Initiatives and Approaches. The book offers a valuable source of research data, information on best practices, and case studies for educators, researchers, Ph.D. students, administrators, and practitioners-and all those who are interested in innovative areas of smart education and smart e-Learning.
Smart Pedagogy for Smart Universities -- Information Channel Based Measure of Effectiveness of Computer-Assisted Assessment in Flipped Classroom -- Efforts for Upward Spirals Based on Both Teacher and Student Feedback on Smart Education -- Analysis of Students' Behaviors in Programming Exercises using Deep Learning -- A Serious Game to Promote Environmental Attitude -- Making MOOCs More Effective and Adaptive on Basis of SAT and Game Mechanics -- The Development of the Critical Thinking as Strategy for Transforming a Traditional University into a Smart University -- RLCP-compatible Virtual Laboratories with 3D-Models and Demonstration Mode: Development and Application in e-Learning -- Remote Laboratory Environments for Smart E-Learning -- An Automata Model for an Adaptive Course Development -- Algorithm of Contextual Information Formation for Smart Learning Object -- Information Technologies in Musical and Art Education of Children -- SPOC produced by sophomores for their junior counterparts -- AnOutcome-based Framework for Developing Learning Trajectories -- Building Smart Learning Analytics System for Smart University -- DILIGO Assessment Tool: A Smart and Gamified Approach for Preschool Children Assessment -- Education Information Interaction in a Group on the Basis of Smart Technologies -- Impact of International Accreditation for Education in the Russian Federation -- User Identification in a Variety of Social Networks by the Analysis of User's Social Connections and Profile Attributes.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence